REVITALISASI NILAI-NILAI KARAKTER NGGUSU WARU SEBAGAI PEMBANGUNAN UTAMA PENDIDIKAN KARAKTER ANAK DI BIMA - Abd Salam (FASHLUNA, 2022)
The fostering of Nggusu Waru values ​​is able to change regeneration for the better. the values ​​contained in nggusu waru are not only character but Islamic values ​​which are believed to be able to protect them from despicable things. With the crisis of character, adab at this time, the main pillars of the sultan and the people of Bima are the Book of Allah (Al-Qur'an) and Al-Hadith besides the guidance and development is "Nggusu Waru". Because nggusu waru has eight character values, namely; 1. Maja Labo Dahu; 2. Dou Mambae Ade; 3. Dou Mambani Labo Disa; 4. Dou Ma Lembo Ade ro Ma Na'e Sabar; 5. Dou Mandinga Nggahi Rawi Pahu; 6. Dou Ma Taho Hidi; 7. Dou ma dou ma di woha dou; 8. Dou monitors ro wara. The values ​​of nggusu waru not only restore the value of commendable character but also restore the former Islamic values ​​and the values ​​of adab which are the main developments in educating, guiding and teaching children as the next regeneration. Because children are not only the successors of the nation but the foundation of the nation. This study focuses on "The character values ​​of nggusu waru as the main development of character education".